Association of Parenting Style with Self-efficacy and Resilience of Gifted and Ordinary Male High School Students in Sari, Iran - Maboudeh Mohammadi; Akram Sanagoo; Abolfazl Kavosi; Ali Kavosi (Golestan University Of Medical Sciences, 2018)
Background and objectives: Parenting style is a determinative and important factor in psychopathology and child development. The quality of parent-child relationship has a significant impact on self-efficacy, happiness and resilience of individuals. The objective of this study was to investigate the relationship between parenting style and self-efficacy and resilience of gifted and normal male students in Sari, Iran.  methods: This descriptive correlational study was performed on 120 gifted students and 120 ordinary male high school students of Sari in 2017. Data were collected using the Baumrind's parenting style questionnaire, Connor-Davidson resilience scale and Sherer's general self-efficacy scale. The data were analyzed by SPSS-16 using descriptive and inferential statistics (Pearson correlation coefficient and t-test). Results: Authoritative parenting style had a significant and positive correlation with students' resilience (P = 0.0001) and self-efficacy (P = 0.0005). There was a significant and negative correlation between the authoritarian and permissive parenting styles and students' resilience (P = 0.0001). In addition, the mean scores of parenting styles, self-efficacy and resilience were significantly different between ordinary and gifted students (P<0.0001). Conclusions: The results of this study indicate the important role of parenting style in the self-efficacy and resilience of students. Therefore, it is recommended to educate parents about positive and constructive parenting styles in order to prevent the consequences of unhealthy parenting styles.